P03.19 Screening for sexually transmitted infections in adolescent girls and young women in mombasa, kenya. (13th September 2015) - Masese, L; Wanje, G; Avuvika, E; Kabare, E; Budambula, V; Mutuku, F; Omoni, G; Baghazal, A; Richardson, BA; McClelland, RS
Abstract : Introduction: As adolescents and young women become sexually active, they are at risk of adverse reproductive health outcomes including sexually transmitted infections (STIs). We assessed feasibility and acceptability of STI screening among 15–24 year-old women in Mombasa County, Kenya. Methods: Participants were recruited from three high schools and one university. Study staff conducted informational sessions. Students interested in participating were given informed assent/consent forms to take home, and asked to visit our clinic for STI screening. During clinic visits, participants completed a self-administered questionnaire and provided a urine specimen to test for Neisseria gonorrhoeae, Chlamydia trachomatis, and Trichomonas vaginalis using the Hologic Aptima Detection System. Results: Between August 2014 and March 2015, 463 high school and 165 university students collected assent/consent forms. Of these, 293 (63%) from high schools versus 158 (95%) from university attended clinic for STI screening (p < 0.001). Of the 153 (34%) who reported any history of insertive vaginal sex, 76 (50%) reported condom use, and 31 (20%) reported hormonal contraceptive use at the last sex act. Twenty-six (5.8%) students had STIs (7 [1.6%] with N. gonorrhoeae, 16 [3.6%] with C. trachomatis and 3 [0.7%] with T. vaginalis ). Older age (OR 1.28; 95% CI 1.07–1.53), reporting vaginal sex (OR 5.89; 95% CI 2.42–14.36), non-penetrative sex (OR 3.47; 95% CI 1.56–7.75), alcohol use (OR 3.34; 95% CI 1.26–8.87), smoking (OR 5.82; 95% CI 1.12–30.37), chewing khat (OR 3.19; 95% CI 1.27–8.01), and being at university rather than high school (OR 4.58; 95% CI 1.94–10.79) were associated with increased likelihood of STI (p ≤ 0.05). Condom use was protective (OR 0.32; 95% CI 0.11–0.94). Conclusion: There was considerable demand for STI screening, and a substantial burden of STIs was observed. These findings support the need for reproductive health interventions to reduce adolescent risk for STIs, pregnancy, and their complications. Disclosure of interest statement: This research was funded by a 2011 developmental grant from the University of Washington Global Centre for Integrated Health of Women, Adolescents, and Children (Global WACh).